1995
DOI: 10.1017/s135561770000014x
|View full text |Cite
|
Sign up to set email alerts
|

The nature of learning and memory impairments in schizophrenia

Abstract: The California Verbal Learning Test was used to characterize the learning and memory impairment in schizophrenia (SC) and to evaluate potential clinical and demographic factors associated with this impairment. SC patients (n= 175) performed worse than normal comparison (NC) subjects (n= 229) on all learning, recall, and recognition memory measures. The most important clinical correlates of these impairments were earlier age of onset, more negative symptoms, and greater anticholinergic medication dosage. SC pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
174
3
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 263 publications
(196 citation statements)
references
References 60 publications
17
174
3
2
Order By: Relevance
“…Our observations are in agreement with several studies reporting verbal learning and memory deficits in SC (Aleman et al, 1999;Hill et al, 2004;Paulsen et al, 1995). Most of these studies found that the verbal memory impairment seen in SC resulted from an encoding deficit, probably caused by the use of ineffective learning strategies.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our observations are in agreement with several studies reporting verbal learning and memory deficits in SC (Aleman et al, 1999;Hill et al, 2004;Paulsen et al, 1995). Most of these studies found that the verbal memory impairment seen in SC resulted from an encoding deficit, probably caused by the use of ineffective learning strategies.…”
Section: Discussionsupporting
confidence: 93%
“…Mori et al (2002) observed a significant improvement in the immediate memory and verbal working memory of SC patients after anticholinergic treatment had been withdrawn for 2 weeks. Other authors have also reported that higher anticholinergic drug dosages are associated with deficits in free recall (Paulsen et al, 1995) and reduced semantic clustering (Strauss et al, 1990).…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…Verbal learning and memory deficits have become a hallmark of schizophrenia research, and an efficient means for evaluating the overall level of cognitive dysfunction in the disorder (Hill et al, 2004b;Paulsen et al, 1995;Saykin et al, 1991). Despite good reliability and moderate to large factor loadings, verbal list learning was only modestly sensitive to change following atypical antipsychotic treatment in both batteries.…”
Section: Psychometrics and Efficiencymentioning
confidence: 99%
“…Verbal episodic memory is particularly affected, with impairment relating in part to use of inefficient organizational strategies (Koh and Peterson, 1978;Paulsen et al, 1995;Iddon et al, 1998). Providing a semantic organizational strategy during word encoding normalizes subsequent recognition accuracy in patients with schizophrenia (Ragland et al, 2003).…”
Section: Introductionmentioning
confidence: 99%